ANALISIS KETERAMPILAN WIRAUSAHA DALAM RANGKA MEMBERDAYAKAN MASYARAKAT (Studi Wirausaha Budidaya Ikan Lele di Desa Negeri Sakti Kecamatan Gedong Tataan Kabupaten Pesawaran) - Armanda, Yuri; Damayantie, Anita (SOCIOLOGIE, 2013)
Problem in this study is How catfish entrepreneurial skills in order to empower the people in the village of Sakti State District Subdistrict Gedongtataan Pesawaran. To learn entrepreneurial skills catfish farming is done in order to empower the people in the village The of Sakti State District Subdistrict gedong Pesawaran settings. The method used was qualitative research, because this research is the process of discovering knowledge that reveals certain situations, especially the catfish pembudiday berakitan with community development, both in terms of economic, psychological, socio-cultural and political. Researchers developed the concept and gather facts, but does not perform hypothesis testing. Data collection techniques consisted of observation and in-depth interviews. From the research that has been done that the skills gained in terms of making alternative feed, regulate and bookkeeping uasaha capital, in terms of the production process include: care, feeding, disease and predators pananggulangan and the next is skilled in marketing. Skills and cultivate innovation in catfish should continue to be developed in accordance with the times and extreme climate change as it is today. With the skill of cultivating catfish makes people more efficient in terms of economic, psychological, socio-cultural, and political.Keywords: Skills and empowerment society